2018
DOI: 10.1186/s12920-018-0436-9
|View full text |Cite
|
Sign up to set email alerts
|

CRlncRC: a machine learning-based method for cancer-related long noncoding RNA identification using integrated features

Abstract: BackgroundLong noncoding RNAs (lncRNAs) are widely involved in the initiation and development of cancer. Although some computational methods have been proposed to identify cancer-related lncRNAs, there is still a demanding to improve the prediction accuracy and efficiency. In addition, the quick-update data of cancer, as well as the discovery of new mechanism, also underlay the possibility of improvement of cancer-related lncRNA prediction algorithm. In this study, we introduced CRlncRC, a novel Cancer-Related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 61 publications
0
20
0
2
Order By: Relevance
“…The advantages of using ML in bioinformatics include the discovery of entirely new information such as arrays of mobile genetic elements, new transposition unit boundaries (Tsafnat et al, 2011), and predicting new long noncoding RNA that are related to cancer (Zhang et al, 2018). Other applications include extracting discriminatory features for automatically determining functional properties of biological sequences (Kamath, De Jong & Shehu, 2014), identifying DNA motifs, which is a difficult task in non-ML applications (Dashti & Masoudi-Nejad, 2010), and automating specific processes like the identification of long non-coding RNAs (Ventola et al, 2017) and the classification of LTR retrotransposons (Arango-López et al, 2017).…”
Section: Publication Identifiermentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of using ML in bioinformatics include the discovery of entirely new information such as arrays of mobile genetic elements, new transposition unit boundaries (Tsafnat et al, 2011), and predicting new long noncoding RNA that are related to cancer (Zhang et al, 2018). Other applications include extracting discriminatory features for automatically determining functional properties of biological sequences (Kamath, De Jong & Shehu, 2014), identifying DNA motifs, which is a difficult task in non-ML applications (Dashti & Masoudi-Nejad, 2010), and automating specific processes like the identification of long non-coding RNAs (Ventola et al, 2017) and the classification of LTR retrotransposons (Arango-López et al, 2017).…”
Section: Publication Identifiermentioning
confidence: 99%
“…Several articles using ML or DL techniques reported that TEs are associated with many human diseases (Zhang et al, 2013). For example, cancer-related long noncoding RNAs have higher SINE and LINE numbers than cancer-unrelated long noncoding RNAs (Zhang et al, 2018). Likewise, several types of epithelial cancers acquire somatic insertions of LINE-1 as they develop (mentioned in Tang et al (2017)).…”
Section: Publication Identifiermentioning
confidence: 99%
“…Several papers using ML or DL techniques reported that TEs are associated with many human diseases (Zhang et al, 2013). For example, cancer-related long noncoding RNAs have higher SINE and LINE numbers than cancer-unrelated long noncoding RNAs (Zhang et al, 2018). Likewise, several types of epithelial cancers acquire somatic insertions of LINE-1 as they develop (mentioned in (Tang et al, 2017)).…”
Section: Benefits Of ML Over Bioinformatics (Q1)mentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are gaining attention because of critical biological functions suggested by recent studies (for a review see (Mercer, Dinger & Mattick, 2009)). Some of the ML applications found included the detection of cancer-related lncRNA (Zhang et al, 2018), the discrimination of circular RNAs from other lncRNAs (Chen et al, 2018), and selection of the most informative features of lncRNA (Ventola et al, 2017). Other applications in the RNA field address the identification and clustering of RNA structure motifs (Smith et al, 2017),…”
Section: Architectures and Algorithms Currently Used For Tes Or Simentioning
confidence: 99%
See 1 more Smart Citation